Detection and Prevention of Black Hole Attack To Improve Network Performance By Using Fidelity and ECARP Algorithms (International Journal of Engineering and Computer Science, 2014)
MANET is a next generation communication network and can be defined by self.Due to its characteristics that is keptattracting for academic research and development.Due their ad hoc nature and dynamic topology, performance and security is a key problem in MANET. In search of secure, efficient and effective algorithm, a simulation is prepared in this paper. This paper describes the detailed analysis and implementation of the proposed work. After implementation, the performance of the designed system is evaluated. according to given results system isadoptable at the performance as well as security point of view